Can We Hear Him Now? James Cone’s Enduring Challenge to White Theologians - Teel, Karen (Theological studies, 2020)
The late great James Hal Cone (1938–2018) challenged white Christians to confront the sin of white supremacy. This article contends that white Catholic theologians collectively have yet to accept Cone’s righteous challenge. A scrutiny of the programming of the annual meetings of the Catholic Theological Society of America and publications in Theological Studies provides the evidence. Having made the case that white US Catholic theologians have not adequately processed Cone’s challenge, the article argues that an important reason for this failure is fear and proposes specific, concrete action steps for professional societies and scholars.